2012
DOI: 10.1177/0748233712448116
|View full text |Cite
|
Sign up to set email alerts
|

Screening of microbial contamination and antimicrobial activity of sea cucumber Holothuria polii

Abstract: Microbiological studies were carried out on microbial contamination and antimicrobial activity of sea cucumber Holothuria polii collected from Mediterranean Sea at Abu-kir shore of Alexandria, Egypt. The obtained results revealed the presence of isolates of five human Gram-negative pathogenic bacteria, representing five genera were identified to species level, including, Esherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella sp. and Shigella sp. In addition, an yeast Candida albicans was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Isolated fungal strains all belonged to the phylum Ascomycota, confirming it as dominant in the marine environment (Jones et al 2019). Our data show a significantly higher fungal diversity (47 species) compared to that reported from previous investigation on the same animal (Omran and Allam 2013) as well as to that reported from other species of sea cucumbers (Pivkin 2000). Omran and Allam (2013) reported only a single isolate, C. albicans, associated with H. poli from the Egyptian Mediterranean Sea, a species not detected in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Isolated fungal strains all belonged to the phylum Ascomycota, confirming it as dominant in the marine environment (Jones et al 2019). Our data show a significantly higher fungal diversity (47 species) compared to that reported from previous investigation on the same animal (Omran and Allam 2013) as well as to that reported from other species of sea cucumbers (Pivkin 2000). Omran and Allam (2013) reported only a single isolate, C. albicans, associated with H. poli from the Egyptian Mediterranean Sea, a species not detected in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Also, it has been reported that holothurin is used in the treatment of asthma, gastric ulcer and high blood pressure (Ridzwan et al, 1990;Kaswandi et al, 1993;Hasan et al, 1996). Moreover, it has antiparasitic and a broad spectrum antifungal effect (Shimada, 1969;Kaswandi et al, 1999;Mona et al, 2012;Omran and Allam, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast (Kabara, 1978) 705 found that the S. japonicus extract has no activity against gram positive and negative bacteria. As well as (Omran and Allam, 2012) showed that the tegument ethanol exctract of Holothuria leucospilata, H. polii, Bohadschia vitiensis and Actinopyga mauri-tania had no antibacterial effects against E. coli (gram negative) and B. subtilus (gram positive). Those variable findings showed that the activity of the extract may be changed according to the method of the extraction (Omran and Allam, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…(Pringgenies and Apriliyani, 2012), sea cucumber Holothuria leucospilota (Pringgenies et al, 2014), Holothuria impatiens (Pringgenies et al, 2015). Two unsaturated fatty acids with potent α-Glusidase inhibitory activity had been purified from the body wall of sea cucumber Stichopus japonicus (Omran and Allam, 2012;McLafferty, 1980). Methanolic extract of Sticopus badionotus showed antibacterial effects against S aureus (Mc-Lafferty, 1980).…”
Section: Discussionmentioning
confidence: 99%